PHYSICAL AND CHEMICAL CHARACTERISTICS OF SEMI-FINISHED BISCUIT WITH THE ADDITION OF CRICKETS FLOUR AND SUGAR SUBSTITUTES DURING STORAGE - SEREDA, OLHA; MELNYK, OKSANA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article is devoted to studying changes in the physicochemical characteristics of the baked semi-finished biscuit with the addition of cricket flour and sugar substitutes during storage. Diabetes is one of the most common chronic diseases in the world. Considering the high incidence of diabetes and obesity, a common practice in the creation of new semi-finished product technologies is to replace sugar with sugar substitutes. Given the earlier creation of the technology, special attention is paid to substitute sugars for sugar substitutes in whipped biscuit semi-finished products, which are quite popular among consumers.When developing whipped biscuit semi-finished products for patients with diabetes, it is advisable to introduce raw materials rich in complete proteins, vitamins, and minerals. Such raw ingredients include cricket flour, which contains up to 70.53% proteins. However, the use of new raw materials caused a change in the organoleptic and physicochemical properties of the baked semi-finished product.Therefore, it was expedient to investigate the physicochemical parameters of the baked whipped biscuit semi-finished product by adding cricket flour and sugar substitutes.The article states that cricket flour, in addition to being high in protein, contains fats, carbohydrates, insoluble fiber, and chitin. The sugar substitutes of the new generation of erythritol and fructose are characterized.According to the results of research, it was found that the complete replacement of sugar with a mixture of erythritol and fructose in the amount of 65:35 in the technology of whipped biscuit semi-finished product with the addition of cricket flour leads to a slight change in the parameters of baking, drying, and elasticity, which indicates the ability of sugar substitutes in the presence of water to retain moisture inside the baked semi-finished product and prevent moisture from evaporating from the biscuit and contribute to preserving its quality by reducing drying.
Keywords: whipped biscuit semi-finished product; flour from crickets; sugar substitutes; erythritol; fructose; baking; drying; crumb elasticity; shelf life